What mothers want: Exploring the policies mothers say would help after the birth of a child - Whitehouse, G; Baird, M; Renda, J; Baxter, Jennifer; Alexander, M (My University, 2008)
The birth of a child brings enormous changes to families, with mothers usually reducing their involvement in the labour market (at least for a period), with the resultant financial pressures that can ensue. This paper considers the extent to which mothers reported certain employment conditions and policy options that would have helped them during these critical months following the birth of a child, using data from the 2005 Parental Leave in Australia Survey. This survey was nested within Wave 1.5 of the Longitudinal Study of Australian Children, and parents of young children (aged 15 to 29 months at the time of the survey) were asked a range of questions about their use of leave and engagement in the labour market around the birth of these children. The policy options addressed were: access to paid and unpaid maternity or paternity leave, better access to part-time work or family leave options, better breastfeeding facilities at work, higher or some maternity payment, and more accessible, affordable or better quality child care. The paper considers whether mothers with particular characteristics (including those of the families they come from) are more likely to have expressed a wish for particular policies.
Keywords: Families -- Mothers; Policy; Families; Families and relationships; Families; Policy; Mothers; Families and relationships